DAMPAK PANDEMI COVID-19 DALAM KEHIDUPAN SOSIAL-EKONOMI MASYARAKAT STUDI KASUS KEHIDUPAN SOSIAL-EKONOMI MASYARAKAT PANDEGLANG BANTEN - Herdin Muhtarom (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
The current Coronavirus (Covid-19) outbreak has become a major focus of the global community because of the many impacts that have been caused by the Covid-19 pandemic, both in the fields of health, social, economics, and education. The purpose of this study was to determine the impact of the Covid-19 pandemic, especially in the economic and social sectors in Pandeglang Regency, Banten. The method used in this study is the Qualitative Descriptive Analysis method. The results showed that the impact of the Covid-19 pandemic greatly affected the economic field in Pandeglang District, especially community income in Pandeglang declined during the Covid-19 pandemic and many large-scale Termination of Work (PHK) felt by the Pandeglang community, for the social sector many communities or the government provided food or basic needs assistance to people in Pandeglang who were affected by the Covid-19 pandemic so that the level of community solidarity during the Covid-19 pandemic in Pandeglang District was very high.